(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current research was prepared to explore the hepato-nephroprotective effect of Lepidium sativum seedaquatic extract against oxidative stress stimulated by dexamethasone in rats. Animals were classified asfollows; group one was used as control while groups 2, 3 and 4 were treated orally with Lepidium sativumseed extract (LSSE; 20 mg/kg, daily), interperitoneally with dexamethasone (DEX; 1 mg/kg BW) andLSSE plus DEX for 14 days, respectively. Administration of DEX elevated thiobarbituric acid reactivesubstances (TBARS), hydrogen peroxide (H2O2), and kidney and liver function biomarkers level, andlactate dehydrogenase activity. While enzymatic (SOD, CAT, GPx, GR, GST) and non-enzymatic (GSH)antioxidants, protein content, and alkaline phosphatase activity were significantly decreased. Otherwise, ratssupplemented with LSSE singly declined lipid peroxidation and improved most of the studied parameters.Moreover, rats pretreated with LSSE then received DEX showed significant alleviation in lipid peroxidation,antioxidant status and biochemical indices with respect to DEX treated group. Conclusively, LSSE hasbeneficial protective effects and has the capability to counteract the harmful influence of DEX. So, Lepidiumsativum might represent a novel approach in the therapy of dexamethasone because of its antioxidantproperties.